THE HAPPINESS OF WOMEN WEARING FACE-VEIL - Amalia Ridha Sudirman; Rena Latifa (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. Around 2017 women wearing face-veil has been increase in Indonesia. Nevertheless, high perceptions and behavioral discrimination are still experienced by most face-veiled women in their daily social life. This can be harming happiness which is an important psychological condition for every individual furthermore. Through sample of 199 participants of early adult women who wearing face-veil from big cities area, OHQ scale (Hills & Argyle, 2002) was used to measure happiness, MMS scale (Dasti & Sitwat, 2014) for Islamic spirituality, and IPC scale (Levenson, 1981) for locus of control. Validity test is done firstly by CFA method and Lisrel software. Then a multiple analysis method (MRA) was carried out to test the effect through SPSS software. Analysis results of this study indicated there is a significant effect of Islamic spirituality and locus of control towards happiness of face-veiled women in big cities, with statistical value at 55.1%. Whereas regression coefficient results showed that four sub-variables that contributed significantly are self discipline, feelings connectedness with Allah, meanness-generosity, and internal locus. The author hopes that the implications of the research results will be reviewed and developed in further research by further examining what factors are the fourth factors and deepening the information on things that will increase happiness, especially in certain groups, such as women wearing face-veil. Abstrak. Sekitar tahun 2017 perempuan yang memakai cadar di Indonesia meningkat. Meski demikian, persepsi dan diskriminasi perilaku yang tinggi masih dialami oleh sebagian besar perempuan bercadar dalam kehidupan sosial sehari-hari. Hal ini dapat merusak kebahagiaan yang merupakan kondisi psikologis penting bagi setiap individu selanjutnya. Melalui 199 sampel partisipan wanita dewasa awal yang memakai cadar dari wilayah kota besar, skala OHQ (Hills & Argyle, 2002) digunakan untuk mengukur kebahagiaan, skala MMS (Dasti & Sitwat, 2014) untuk spiritualitas Islam, dan skala IPC. (Levenson, 1981) untuk lokus kendali. Uji validitas dilakukan terlebih dahulu dengan metode CFA dan software Lisrel. Kemudian dilakukan metode analisis berganda (MRA) untuk menguji pengaruh tersebut melalui software SPSS. Hasil analisis penelitian ini menunjukkan bahwa terdapat pengaruh yang signifikan antara spiritualitas Islam dan locus of control terhadap kebahagiaan perempuan bercadar di kota-kota besar, dengan nilai statistik sebesar 55,1%. Sedangkan hasil koefisien regresi menunjukkan bahwa empat sub variabel yang memberikan kontribusi signifikan adalah disiplin diri, perasaan keterhubungan dengan Allah SWT, sifat-sifat murah hati, dan lokus internal. Penulis berharap implikasi dari hasil penelitian di kaji kembali dan dikembangkan pada penelitian selanjutnya dengan meneliti lebih lanjut fator-faktor apa saja yang menjadi penyebab keempat variabel ini serta memperdalam informasi hal-hal yang akan meningkatkan kebahagiaan terutama pada kelompok tertentu, seperti wanita bercadar.